ANALISIS STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SDN 200212 PADANGSIDIMPUAN SELATAN - Melita Batubara; Sri Wahyunigsi Sibagariang (Yayasan Baitul Hikmah al-Zain, 2025)
This study aims to describe and analyze the strategies implemented by teachers in improving students' learning motivation at SDN 200212 Padang Sidempuan Selatan. Learning motivation is a key factor in determining the success of the learning process, especially at the elementary school level where the characteristics of students are still in the early stages of cognitive, affective, and psychomotor development. This study uses a qualitative approach with a descriptive method, involving observation techniques, interviews with class teachers, students, and principals, and documentation studies. The results of the study indicate that teachers use various creative and innovative learning strategies to improve students' learning motivation, including through the use of active learning methods such as educational games, integrative thematic approaches, interesting and simple technology-based learning media, and giving awards as a form of positive reinforcement